Neural correlates of successful costly punishment in the Ultimatum game on a trial-by-trial basis. Issue 6 (25th January 2022) - Mussel, Patrick; Weiß, Martin; Rodrigues, Johannes; Heekeren, Hauke; Hewig, Johannes
Abstract: Costly punishment describes decisions of an interaction partner to punish an opponent for violating rules of fairness at the expense of personal costs. Here, we extend the interaction process by investigating the impact of a socio-emotional reaction of the opponent in response to the punishment that indicates whether punishment was successful or not. In a modified Ultimatum game, emotional facial expressions of the proposer in response to the decision of the responder served as feedback stimuli. We found that both honored reward following acceptance of an offer (smiling compared to neutral facial expression) and successful punishment (sad compared to neutral facial expression) elicited a reward positivity, indicating that punishment was the intended outcome. By comparing the pattern of results with a probabilistic learning task, we show that the reward positivity on sad facial expressions was specific for the context of costly punishment. Additionally, acceptance rates on a trial-by-trial basis were altered according to P3 amplitudes in response to the emotional facial reaction of the proposer. Our results are in line with the concept of costly punishment as an intentional act following norm-violating behavior. Socio-emotional stimuli have an important influence on the perception and behavior in economic bargaining.